Pelatihan Pembuatan Eco-Enzyme sebagai Alternatif Pembelajaran Sains Fun Learning di Masa Transisi Pandemi Covid-19 pada Masyarakat Dusun Aik Gamang Kabupaten Lombok Tengah - Suryati, Suryati; Salim, Agus; Mashami, Ratna Azizah; Sundari, Emi (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2023)
The Covid-19 pandemic has reduced children's learning motivation in Aik Gamang Hamlet, Ranggagata Village, Central Lombok Regency. To overcome this problem, socialization and training activities were carried out on making eco-enzymes as an alternative to fun learning science during the transition period of the Covid-19 pandemic. Eco-enzyme is an organic solution produced from fresh vegetable waste, fruit waste, brown sugar and water using selective microorganisms. This activity aims to raise children's enthusiasm, build positive social interactions with parents, and educate housewives to utilize household organic waste into something more useful. The problem solving method is carried out through pre-socialization stages, preparing brochures, collecting materials, core activities, and evaluation for 1 week. As a result, two 600 ml bottles of eco-enzyme were obtained, and it is hoped that eco-enzyme production can continue to be carried out through waste banks. Apart from that, hand sanitizer was also made from aloe vera extract, as well as planting hydroponic plants. Discussions involve active community participation in this activity. From this activity, it can be concluded that training in making eco-enzymes and related activities can be an innovative solution to increase children's learning motivation, strengthen social interactions, and educate the public in utilizing organic waste.